Face Threatening Acts in Pre-Service Teachers and Students: A Case Study in EFL Classroom - Jimmy Sapoetra (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, 2021)
Maintaining relationship between teachers and students is one of the key issues in Education. This issue is important as the relationship affects the process as well as the results of students’ learning. It is also significant how the teachers interact with the students in the classroom. In this study we would like to see whether teachers’ attitude affects students’ perception on such a behavior. This was seen through the language that teachers use in the classroom. Some teachers tend to use face threatening acts (FTA), which cause the students feel uncomfortable, tense, and anxious (Pomerantz 1984, Beebe & Cummings 1985, Chen, 2006). As a result, the students’ learning outcomes might be affected. In some cultures, doing such a thing would be considered impolite. The study was conducted in one of the private senior high schools in Jakarta with a sample of two teachers and 50 students of Grades 10 & 11 from two EFL classrooms. The study used qualitative and quantitative approach with descriptive statistics to analyze the findings. A list of questionnaires was used along with an interview with the two teachers to clarify the results. The discussion covered several aspects regarding the existence of FTA in EFL classrooms: the kinds of threatening acts used, the patterns of the threatening acts, the factors of using threatening acts, and the students’ responses of threatening acts. The study was expected to give insights for the pre-service teachers in EFL classroom.